Situatedness for global display web apps - Taivan, Constantin (2013)
Most display systems are making use of static definition for the places in which they are situated. The content shown on these displays is predefined as is the case of television broadcasting. In this paper we present an approach that allows local display managers, e.g., display owners, to instantiate global display web applications on each display basis. We describe an innovative model for content presentation that takes into consideration both the display environmental data, e.g., sensors and user interactions, and app specific configuration. This approach enables the content being shown to be highly personalized, thus reflecting the dynamic and situated behavior of global display web apps.